As interfaces teórico-práticas entre a economia criativa e a educação profissional e tecnológica - Costa, Lucyane Maria Castro (2021)
This dissertation aimed to research the theoretical-practical links between Creative Economy and Professional and Technological Education, that is, to make connections between the productive and educational structures, strengthening them. For this, the study sought new forms of professional performance beyond salaried employment as the only representative form of work for students. Nowadays, both formal education and the corporate world do not prepare the individual to be an entrepreneur. Therefore, the meaning of work needs to be expanded to reach its fullness and represent the resumption of the means of production, so that work through entrepreneurial activity is seen as this opportunity; in addition to achieving the independence, emancipation, and empowerment of individuals. Therefore, a work-oriented education is the possibility of connecting with a real-world activity, promoting the development of the student's abilities, as legitimate knowledge will be extracted from this practice, not simulated. The methodology used was the Discursive Textual Analysis with the aid of the bibliographic-conceptual method. A vast number of theoretical inputs, from national and international literature, was brought together to build a robust theoretical framework. The scientific dimension was completed with field research. The results achieved with the empirical survey contributed to the proposal of the educational product. Through them, exploratory research was possible by gathering data collected using a semi-structured questionnaire. The interfaces of understanding between the main themes of the study: Entrepreneurship, Innovation, Creativity, Economy, Professional and Technological Education and Integrated High School were being built. The results pointed to the making of a business plan as the most effective content to be worked with students, as it is also connected with the pedagogical principles of the integrated curriculum, such as: the inseparability of theory and practice, interdisciplinarity, work as an educational principle and integral human formation; it becomes another possible career path for students. Thus, the educational product was planned as a proposal to be used to stimulate and equip Integrated High School students to deal with creative entrepreneurship. EPTCanvas for business: an economically creative ebook, it is instructional material to help transform ideas and ideals into a business reality